IMPACT OF LONG-TERM IONIZING RADIATION ON GERMINATION AND GERMINATING ABILITY OF THE COMMON REED’S SEEDS - Гудков, Д.; Шевцова, Н.; Явнюк, А. (Proceedings of National Aviation University, 2012)
Methodology and results of common reed reproductive characteristics investigation in water bodies with different level of radionuclide contamination are represented in the work. The aim of the work is to study peculiarities of response of  higher aquatic plants, by the example of the  common reed, on long-term ionizing radiation exposure at genetic, morphological and reproductive levels. The matter of research is a generative reproduction and growth processes of the common reed under conditions of ionizing radiation stress. The research was  carried out with the use of  laboratorial seeds cultivating method. Doses absorbed by plants were assessed with the help of methodology using dose conversion coefficients. The obtained research data about liability and  abnormalities of common reed’s germs in water bodies with different level of radionuclide  contamination testify about considerably high level of low doses long-term exposure efficiency for indexes of germination and germinating ability of seeds